Revision of Australian Brachysandalus with the description of nine new species including one cavernicolous species (Hemiptera: Heteroptera: Reduviidae), and observations on male extragenital structure and leg teratology - Malipatil, M. B.; Liu, Yingqi; Cai, Wanzhi (Zootaxa, 2024)
The Australian species of the genus Brachysandalus Stål, 1867 (Hemiptera: Heteroptera: Reduviidae: Peiratinae) are revised. A total of 21 species are recognised, including nine new species: B. ayyammae Malipatil & Liu, sp. nov., B. flavidus Malipatil & Liu, sp. nov., B. fulvipes Malipatil & Liu, sp. nov., B. gunbalanyae Malipatil & Liu, sp. nov., B. howarthi Malipatil & Liu, sp. nov., B. longifemoratus Malipatil & Liu, sp. nov., B. maculatus Malipatil & Liu, sp. nov., B. pallidus Malipatil & Liu, sp. nov. and B. westraliensis Malipatil & Liu, sp. nov. Redescriptions of the genus Brachysandalus and all 12 previously described Australian species of the genus as recognised in this study, are presented. Lectotypes are designated for Brachysandalus helluo Stål, 1867, B. lurco Stål, 1867, B. punctorius Stål, 1867, Pirates (Brachysandalus) alutaceus Reuter, 1881, P. (Brachysandalus) brevicoxis Stål, 1874, P. (Brachysandalus) crassifemur Reuter, 1881, P. (Brachysandalus) flavo-pictus Stål, 1874, P. (Brachysandalus) limbatus Reuter, 1881, P. (Brachysandalus) melanolestoides Stål, 1874, P. (Brachysandalus) setosus Stål, 1874, P. fuliginosus Erichson, 1842, P. fulvipennis Walker, 1873, P. sepulchralis Distant, 1902 and Reduvius (Pirates) ephippiger White, 1843. Pirates fulvipennis Walker, 1873 is removed from synonymy with B. punctorius Stål, 1867, and revalidated with the new combination as B. fulvipennis (Walker, 1873), stat. rev. & comb. nov. Pirates (Brachysandalus) flavopictus Stål, 1874, is removed from synonymy with B. punctorius Stål, 1867, and confirmed as synonym of B. fulvipennis (Walker, 1873). Reduvius semifasciatus Walker, 1873 is removed from synonymy with Brachysandalus fuliginosus (Erichson, 1842), and because the former not considered to be a peiratine species is placed here as “Incertae sedis”. Pirates erythromelas Walker, 1873 is transferred to Brachysandalus as B. erythromelas (Walker, 1873), comb. nov. A key to species is provided together with images of the habitus of type specimens and some other males and females with different wing forms, and major structures of male genitalia to assist distinguishing these species. Based on morphology, brief comments are provided on putative species groups within the studied species. Brachysandalus howarthi Malipatil & Liu, sp. nov. collected from Bayliss Cave, north Queensland, is morphologically and behaviourally adapted to live in caves and is regarded to be an obligate subterranean species, further details and some biological information is provided. Detailed observations of the male extragenital structure that is present on the left side of sternite VII, were made in all species of Brachysandalus considered in the present study. Fourteen of the 21 species studied have been recorded to possess an externally visible extragenital process, that varies greatly in size, shape and development between species; these details are illustrated and discussed including their probable function in mating process, and potential value in species diagnoses. Cases of leg teratology, specifically morphological abnormalities of tarsi and tarsal claws, were observed in a few specimens of four species, i.e., Brachysandalus lurco Stål, 1867, B. helluo Stål, 1867, B. flavidus Malipatil & Liu, sp. nov. and B. gunbalanyae Malipatil & Liu, sp. nov.; details are illustrated and discussed.